Economic geography : real or hype? - Koo, Jun (Policy research working paper, 2004)
"Economic geography has become a mantra for many economists, geographers, and regional scientists. Previous studies have tested the importance of economic geography for production activities and found a significant association between them. Most of these studies, however, have not taken into account that economic geography influences location decisions at the firm level. Koo and Lall show a potential bias that can arise when firm location choices are not considered in estimating the contribution of economic geography to industry performance. Their analysis using microdata of Indian manufacturing firms shows there is an upward bias in the contribution of economic geography to productivity when firm location choices are not considered in the analysis. This paper--a product of the Infrastructure and Environment Team, Development Research Group--is part of a larger effort in the group to examine industry location decisions. The study was partly funded by the Bank's Research Support Budget under the research project "Urbanization and the Quality of Life."--World Bank web site